APERIODIC OPTIMAL CHECKPOINT SEQUENCE UNDER STEADY-STATE SYSTEM AVAILABILITY CRITERION - IWAMOTO, K.; MARUO, T.; OKAMURA, H.; DOHI, T. (Advanced Reliability Modeling II, 2006)
In this paper, we develop a computation algorithm for an aperiodic checkpoint placement problem with a preventive maintenance, which maximizes the steady-state system availability. The proposed algorithm is based on the usual dynamic programming, and provides an effective iterative scheme. In a numerical example, we investigate the dependence of model parameters on the optimal checkpoint sequence, and carry out the sensitivity analysis to examine the effects of failure parameter and the preventive maintenance time.